MOTIVASI PENDIDIKAN DALAM AL-QURAN DAN HADITS - Pausil; Syafruddin; Zulheldi; Rehani (As-Sulthan Journal of Education, 2026)
The Qur'an provides a very strong motivational basis for education. The verses regarding the command to read (sura al-Alaq verses 1-5), think (sura az-Zumar verse 9), and seek knowledge (sura at-taubah verse 122) contain encouragement that awakens enthusiasm for learning. Apart from that, Allah's promise to raise the status of those with knowledge (Al-Quran surah al-Mujadilah verse 11) becomes a religious stimulus that strengthens students' motivation. The Al-Qur'an also presents the targhib (promise of reward) method (Al-Quran Surah Fatir verses 29-30) and tarhib (warning of punishment) as a balanced motivational approach, so that students are not only driven by the hope for goodness, but also by awareness of the consequences if they neglect to seek knowledge. The hadith of the Prophet sallallaahu alaihi wasallam complements the Qur'anic motivation by emphasizing the obligation to seek knowledge, the primacy of ulama, and the encouragement to continue learning throughout life. These hadiths clearly demonstrate that Islam places education as a highly valued form of worship in the sight of Allah. The Prophet's motivational messages also emphasize that knowledge is light, while ignorance is darkness, making the pursuit of knowledge a path to enlightenment. The exemplary behavior of the Prophet and his companions also serves as practical motivation for students to embrace knowledge as a way of life.